2004
DOI: 10.1080/09286580490515170
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic conditions as determining factors in the prevalence of systemic and ocular toxoplasmosis in Northeastern Brazil

Abstract: The prevalence of systemic toxoplasmosis, although high, was lower than that found in studies performed in the South and Southeast of Brazil, and the incidence of ocular lesions was totally different, being lower by a factor varying from 5 to 17. Although important epidemiological variables, such as owning a cat, drinking unfiltered water or having had contact with lakes or rivers, were found to be correlated with toxoplasmosis in the preliminary analysis, they lost their influence when included in the logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 14 publications
2
25
0
7
Order By: Relevance
“…A high seroprevalence of infection with T. gondii in children (40%) and teenagers (60%) has been reported in Fortaleza and others parts of Brazil. 18,[25][26][27] The overall prevalence in pregnant women from our study was 69%, which was slightly higher than that observed in teenagers. The increase in prevalence with age is consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 79%
“…A high seroprevalence of infection with T. gondii in children (40%) and teenagers (60%) has been reported in Fortaleza and others parts of Brazil. 18,[25][26][27] The overall prevalence in pregnant women from our study was 69%, which was slightly higher than that observed in teenagers. The increase in prevalence with age is consistent with results of previous studies.…”
Section: Discussionmentioning
confidence: 79%
“…Poor socioeconomic conditions that are characterized by overcrowding and a lack of hand hygiene, and placing children in daycare facilities, promote CMV transmission 63. Low socioeconomic status is also associated with T. gondii infection,57,6466 which may explain why persons with positive CMV serostatus were more likely to be seropositive for T. gondii IgG antibodies. The HSV-1 is an alpha-herpes virus that produces orolabial blisters or lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is a leading cause of blindness in Brazil[1] but not in Europe or North America [2],[3]. These differences are not adequately explained by high rates of postnatal or congenital infection in Brazil, as similar rates of infection have been observed in France and Eastern Europe [4][8]. Once infected, population-based studies of adolescents and adults, most of whom have postnatally acquired infection, report the risk of retinochoroiditis to vary from 2% in North Eastern Brazil to 25% in Southern Brazil [4], [9][11].…”
Section: Introductionmentioning
confidence: 99%